Mechanisms determining a differential threshold for sensing Src family kinase activity by B and T cell antigen receptors - Borna, Simon; Fabisik, Matej; Ilievova, Kristyna; Dvoracek, Tomas; Brdicka, Tomas (The Journal of biological chemistry, 2020)
Although signal transduction by immunoreceptors such as the T cell antigen receptor (TCR), B cell antigen receptor (BCR), and Fc receptors uses the same schematic and similar molecules, the threshold and the fine-tuning are set differently for each receptor. One manifestation of these differences is that inhibition of Src family kinases (SFK) blocks TCR but not BCR signaling. SFKs are key kinases phosphorylating immunoreceptor tyrosine-based activation motifs (ITAM) in both these receptors. However, it has been proposed that in B cells, downstream kinase SYK can phosphorylate ITAM sequences independently of SFK, allowing it to compensate for the loss of SFK activity, whereas its T cell paralog ZAP-70 is not capable of this compensation. To test this proposal, we examined signaling in SYK- and ZAP-70-deficient B and T cell lines expressing SYK or ZAP-70. We also analyzed signal transduction in T cells expressing BCR or B cells expressing part of the TCR complex. We show that when compared with ZAP-70, SYK lowered the threshold for SFK activity necessary to initiate antigen receptor signaling in both T and B cells. However, neither SYK nor ZAP-70 were able to initiate signaling independently of SFK. We further found that additional important factors are involved in setting this threshold. These include differences between the antigen receptor complexes themselves and the spatial separation of the key transmembrane adaptor protein LAT from the TCR. Thus, immunoreceptor sensing of SFK activity is a complex process regulated at multiple levels.
Keywords: receptor regulation; SYK-family kinases; Receptors, Antigen, T-Cell; Jurkat buňky; signal transduction; T-cell receptor (TCR); Syk Kinase; lidé; calcium; signální transdukce; Signal Transduction; T-lymfocyty; inhibitor; receptory antigenů T-buněk; Receptors, Antigen, B-Cell; protein-tyrosinkináza ZAP-70; tyrosine-protein kinase (tyrosine kinase); skupina kinas odvozených od src-genu; B-Lymphocytes; src-Family Kinases; B-lymfocyty; receptory antigenů B-buněk; kinasa Syk; B-cell receptor; adaptor protein; Src-family kinases; T-Lymphocytes; Jurkat Cells; ZAP-70 Protein-Tyrosine Kinase; Humans